Changes in Abortion in Texas Following an Executive Order Ban During the Coronavirus Pandemic - White, Kari (JAMA, 2021)
This study assesses changes in abortions performed and at what gestational age following a Texas order postponing non–medically necessary surgeries due to the COVID-19 pandemic compared with abortions performed during the same months in 2019.